A Retrospective Review of Bladder Cancer at Charlotte Maxeke Johannesburg Academic Hospital-University of The Witwatersrand - (2010–2020) - Oliver, Trenton Luke (University of the Witwatersrand, Johannesburg, 2023)
Introduction: Bladder cancer is among the most common urological cancers and the leading cause of cancer mortality worldwide. It is particularly prevalent in High-Income Countries (HICs), although its incidence is rising in Low-and-middle -income countries (LMICs). This review describes the profile, clinical presentation, and management of our institution's bladder cancer patients. Method: A retrospective review of patients aged 18 years and above who were diagnosed with bladder cancer and managed at the Radiation Oncology department of Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) from January 2010 to December 2020. Data were collected on demographics, risk factors, clinic-pathological features, and specific therapies received by these patients. A comparison was made between patients presenting with squamous cell carcinoma and translational cell carcinoma of the bladder. Results: Among 115 patients, the median age ± standard deviation was 60.7 ± 14.9, and 60.9% were males with a male-to-female ratio of 1.6:1. Few patients (4.4%) had a history of schistosomiasis, and 47.8% had a history of smoking. Tumour histology included transitional cell carcinoma (TCC) in 78 (67.8%), squamous cell carcinoma (SCC) in 31 (27.0%), and atypical tumour in 6 (5.2%). Most patients presented with Muscle-Invasive Bladder Cancer (MIBC) (61 (53.0%)) followed by Metastatic Urothelial Cancer (MUC) (n=52, 45.0%), while the remaining 2.0% (n=2) had Non-Muscle Invasive Bladder Cancer (NMIBC). More than half of the patients (59.1% n=68) had palliative treatment, 26 (22.6%) had radical treatment, and 21 (18.3%) patients did not receive radiotherapy. Patients who presented with TCC were more likely to be older (odd ratio (OR): 1.03, 95% Confidence Interval (CI): 1.01–1.06, p=0.029), male (OR: 2.60, 95% CI:1.10–6.04, p=0.030), predominantly of the black population, but white patients are four times more likely to present with TCC than SCC (OR:4.22, 95% CI: 1.43–12.48, p=0.009). Conclusion: The prevalence of TCC is still higher in our centre compared to SCC. Although the burden of bladder cancer is highest in HICs, with increasing exposure to risk factors, a shift is gradually experienced in LMICs.
A Research Report Submitted in fulfilment of the requirements for the Degree of Master of Medicine (M. Med) in the branch of Radiation Oncology, to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Bladder cancer; Radiation Oncology; High-Income Countries (HICs); Low-and-middle -income countries (LMICs); Charlotte Maxeke Johannesburg Academic Hospital (CMJAH); Non-Muscle Invasive Bladder Cancer (NMIBC; Transitional cell carcinoma (TCC); Muscle-Invasive Bladder Cancer (MIBC); Metastatic Urothelial Cancer (MUC); Squamous cell carcinoma (SCC); SDG-3: Good health and well-being; SDG-4: Quality education